Hepatology and The Canadian Gastroenterologist: Interest, Attitudes and Patterns of Practise: Results of a National Survey from the Canadian Association of Gastroenterology - Vincent G Bain; Winnie W Wong; Paul D Greig; Eric M Yoshida (Canadian Journal of Gastroenterology)
BACKGROUND: Hepatology has emerged as a subspecialty distinct from gastroenterology. Despite this, there is no formal certification examination or accredited training program, and training remains combined with gastroenterology.